‘Male Gaze’ in Bollywood Item Songs: A Study of Popular Song Munni Bodnam Hui of Dabang (2010) Movie - Khalilullah Muhammad Bayezid; Fahmida Hossain; Sumaya Hasin (CenRaPS Journal of Social Sciences, 2022)
The importance of item songs along with the excellent story is on the increase in contemporary cinemas, especially in Bollywood cinemas. In these songs, the presence of recent heroines is very much noticeable, and even many cinemas get the promotion centering on the item songs where the erotic demonstration of the female character gets more preference. In these songs, the heroine is nothing but a product to be entertained, and the males are the spectators. According to Laura Mulvey, if a woman is presented in the way ‘the spectators want to look at is identical to the male gaze. In this article, a famous Bollywood item song has been selected to analyze based on the Theory of Male Gaze by Mulvey.